PERLINDUNGAN HUKUM TERHADAP WARTAWAN MENURUT UNDANG-UNDANG PERS NOMOR 40 TAHUN 1999 DI KOTA SAMARINDA - Nelfianti Narulita (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT The development of mass media today is very rapid to be accepted and consumed by the public. The press and mass media are also very supportive for the success of state development in addition to the facilities that support the implementation of other development. As for the problems in this research is the rule of law concerning violence committed against journalists who are carrying out their duties and profession and legal protection against journalists who received violence in performing their duties according to Law Number 40 Year 1999. This research includes empirical normative legal research , including positive law research, legal principles, clinical law research, systematic legislation, synchronization of a legislation and field research. Law Number 40 Year 1999 regarding the Press. Law Number 39 Year 1999 on Human Rights. The results showed that the causes of violence against journalists are internal factors, the unprofessionality of journalists. External factors. Journalists who do not work in accordance with journalistic code of ethics and Law no. 40 Year 1999. Keywords: Journalist, Press, Legal Protection, Mass Media